Academic Staff Involvement and Openness to Diversity in International Educational Organisations: Is There a Moderating Effect of Shared Language?. (2nd April 2013) - Selmer, Jan; Lauring, Jakob; Jonasson, Charlotte
Abstract Joint work among academic staff is important for solving the ever‐increasing number of complex tasks that are becoming part of everyday activities in higher education. At the same time, diversification and internationalisation may challenge collaboration processes and communication demands. Speaking a shared language consistently could be a way of overcoming problems. Hence, this study focuses on the effect of shared language among academic staff on the relation between academic staff involvement in work processes and openness to diversity. This study draws on data from 489 Danish academic staff members in science departments of three universities. Results show positive associations between academic staff involvement and all openness‐to‐diversity variables (openness to informational, linguistic, value and visible diversity). Shared language had a positive effect on openness to surface level types of diversity (linguistic and visible) but no effect on openness to deep‐level types of diversity (informational and value).